Compliance with food safety practices among smallholder dairy farmers in Bihar, India: Drivers and impact - Kumar, Anjani; Saroj, Sunil; Thapa, Ganesh B.; Joshi, Pramod Kumar; Roy, Devesh (International Food Policy Research Institute, 2017)
The demand for compliance with food safety measures (FSM) at farm level, an integral component of food security, is increasing. Yet, literature on the assessment of FSM at the farm level is scarce, especially for developing countries. To bridge the gap, this study investigates the status, estimates the cost, identifies the determinants, and analyzes the impact of compliance with food safety measures (FSM), using cross-sectional data from a survey of 684 dairy farmers in India. We use an ordinary least square (OLS) regression to examine the drivers of FSM adoption and we use the dose response function (DRF) technique to estimate the impact of FSM adoption on milk yield and profitability. The empirical results reveal that compliance with FSM at the farm level is low, with wide variations among milk producers. Drivers of FSM adoption include education, income, training, herd size, landholding, proportion of self-consumed milk, and households' perception of food safety. The DRF estimates reveal the positive impact of FSM adoption on milk yield and milk profitability.